Correlation of disk configuration to therapeutic success rate in patients with closed lock of the temporomandibular joint - SEGAMI, Natsuki; MURAKAMI, Ken-Ichiro; MORIYA, Yoshiyuki; IIZUKA, Tadahiko; CHEN, Wen-Hsi; FUJIMURA, Kazuma; MIYAKI, Katsuaki (Journal of the Japanese Society for the Temporomandibular Joint, 1990)
The purpose of this study is to clarify the correlation with disk deformity to therapeutic effect in internal derangement with closed lock of the temporomandibular joint (TMJ). The subjects were 96 joints in 89 patients, which morphologically devided into three types of disk configuration by means of double spacing arthrotomography, the first type-prolonged disk (39 joints), second type-folded disk (11 joints), and third type-massed disk (46 joints). The treatment modalities and each success rate were mandibular manipulation technique (49.0%), pumping manipulation (29.5%), anterior repositioning splint therapy (0%), arthroscopic lysis and lavage technique (80%), and open arthrotomy of the TMJ (90.9%). The total therapeutic success rate was 90.0%, consisted of first type with 97.4%, second type with 72.3%, and third type with 87.0%. In manipulation and pumping manipulation technique, success rates of the third type were statistically smaller (34.8%, 16%) than the rares of the first type (64.1%, 50%) and first type+second type (62%, 33.3%). These results indicate that the joint with massed disk is thought to be the most advanced disease, and is indicated for surgical therapy in selected cases.